ANALISIS INPUT OUTPUT PROVINSI JAWA BARAT - Wawan Hermawan (Center for Economic Studies Universitas Katolik Parahyangan, 2006)
Jawa Barat Province has the rapid growth for industrial sector in 2001-2003. This sector will influence to another sector to make a simultaneous growth for the whole economy. This research tries to analyze and explore the structure of industrial sector in Jawa Barat province. The tools to make a figure out of industrial sector in Jawa Barat province is Input Output Model with backward and forward linkages. The data is Input output table Jawa Barat 2000. The important for this research is the highest linkage (backward or forward) are food industry, textile etc.